Predictive value of 3+ spot urinary protein value measured by dipstick in hypertensive pregnant patients. (May 2013) - Şükür, Yavuz Emre; Yalçin, İbrahim and Kahraman, Korhan and Bayramov, Vugar and Özmen, Batuhan and Atabekoğlu, Cem Somer and Söylemez, Feride
Abstract : Objective : To evaluate whether the spot urinary protein (SUP) level has predictive value on pregnancy outcomes in hypertensive pregnant patients. Methods : Retrospective case–control study of 109 pregnant patients with hypertension and spot urinary proteinuria measured by dipstick. Results : Presence of 24 h proteinuria was higher in patients with 3+ SUP. Gestational age at delivery was significantly lower in patients with 3+ SUP when compared with patients with ≤2+ SUP ( p = 0.009). Rate of SGA babies was higher in patients with 3+ SUP when compared with patients with ≤2+ SUP ( p < 0.001). Conclusion : Although it cannot replace 24 h urinary protein determination, 3+ proteinuria with dipstick may have a prognostic value, particularly in emergency cases.